Efektivitas Sabun Antibakteri Kombinasi Ekstrak Serai (Cymbopogon citratus) dan Kitolod (Isotoma longifera (L). Presl.) Terhadap Staphylococcus aureus dan Escheriachia coli - Jannah, Finda Dwi Faridatul; Prasidya, Denaya Andrya; Sulistiono, Eko; Wicaksono, Rizky Rahadian; Hanif, Muhammad (Jurusan Kesehatan Lingkungan Poltekkes Kemenkes Makassar, 2024)
The soap currently on the market contains triclosan, a chemical that can disrupt the endocrine system and poses risks to human health and the environment. Despite Indonesia's wealth of medicinal and herbal plants, their potential has not been maximized. Therefore, this research aims to fully utilize the antibacterial properties of lemongrass (Cymbopogon citratus) and kitolod (Isotoma longifera) leaf extracts against Staphylococcus aureus and Escherichia coli. This research constitutes a true experimental study. The study involves crafting soap from paper using lemongrass leaf extract and kitolod leaf extract, with varying percentages for each. An assessment of the soap preparations over 14 days revealed that the pH decreased while still meeting the requirements of SNI 2588:2017. The foam stability meeting the standard quality is only found in soap with formula I, which does not comply with the quality standard due to prolonged storage. Notably, formula III demonstrated substantial inhibitory effects against Staphylococcus aureus bacteria, making it the most optimal formula. Formula III, containing a mixture of 40% lemongrass leaf ethanol extract and 90% kitolod leaf extract, met all specifications required by SNI 2588:2017 and effectively inhibited the growth of both Staphylococcus aureus and Escherichia coli. Keywords: antibacterial soap; lemongrass; kitolod; Staphylococcus aureus; Escherichia coli.